Effect of Protective Coatings in Welded Constructions on Welding Stability and Electrode Metal Transfer into a Weld Pool in MMA; Solid State Phenomena; Vol. 303 - Ilyashchenko D. P. Dmitry Pavlovich; Chinakhov D. A. Dmitriy Anatol'evich; Verkhoturova E. V. Elena Vladimirovna; Mamadaliev R. A. Rasul Akhmadovich (2020, 2020)
Title screen